Influence of Alkyl Substitution Position on Wide‐Bandgap Polymers in High‐Efficiency Nonfullerene Polymer Solar Cells. Issue 21 (9th August 2020) - Guo, Qing; Li, Wanbin; Li, Guangda; Wang, Kun; Guo, Xia; Zhang, Maojie; Li, Yongfang; Wong, Wai‐Yeung
Abstract: Two wide‐bandgap (WBG) conjugated polymers (PBPD‐ p and PBPD‐ m ) based on phenyl‐substituted benzodithiophene (BDT) with the different substitution position of the alkyl side chain and benzodithiophene‐4, 8‐dione (BDD) units are designed and synthesized to investigate the influence of alkyl substitution position on the photovoltaic performance of polymers in polymer solar cells (PSCs). The thermogravimetric analysis, absorption spectroscopy, molecular energy level, X‐ray diffraction, charge transport and photovoltaic performance of the polymers are systematically studied. Compared with PBPD‐ p, PBPD‐ m exhibits a slight blue‐shift but a deeper highest occupied molecular orbital (HOMO) energy level, a tighter alkyl chain packing and a higher hole mobility. The PBPD‐ m ‐based PSCs blended with acceptor IT‐4F shows a higher power conversion efficiency (PCE) of 11.95% with a high open‐circuit voltage ( V oc ) of 0.88 V, a short‐circuit current density ( J sc ) of 19.76 mA cm −2 and a fill factor (FF) of 68.7% when compared with the PCE of 6.97% with a V oc of 0.81 V, a J sc of 15.97 mA cm −2 and an FF of 53.9% for PBPD‐ p . These results suggest that it is a feasible and effective strategy to optimize photovoltaic properties of WBG polymers by changing the substitution position of alkyl side chain in PSCs. Abstract : Two wide bandgap conjugated polymers PBPD‐ p and PBPD‐ m with alkyl side chains substituted at the para ‐position and meta ‐position, respectively, are synthesized. Compared with PBPD‐ p, the devices based on PBPD‐ m exhibit a higher efficiency of 11.95% with increased open‐circuit voltage, short‐circuit current density, and fill factor, simultaneously.